Successful Prevention and Youth Development Programs - Ferrer-Wreder, Laura. author. aut Link
XX, 339 p.
Keywords: From a European Perspective This book charts territory that is profoundly important, and yet rarely fully understood. The authors have attempted a task that has relevance to the widest possible range of professionals working with children and adolescents. In describing and assessing the fields prevention and promotion they have performed an immense service to researchers in this field, but also to practitioners across the spectrum, from mental health nurses and doctors to teachers and psychologists, from social work professionals to psychiatrists and youth counselors. There are two other key elements that should be emphasized from the outset. The first is that the approach in this book is truly multi-disciplinary, with the authors making a genuine attempt to draw upon knowledge and practice derived from all the relevant disciplines. The second element which makes this book so important is that the authors have worked across countries, to ensure that work in the field of intervention from both North America and from Europe should be included. This is as welcome as it is refreshing. There appear to be so many barriers to true collaboration between the two continents, and so many examples of either North American to what is going on "across the or European social scientists appearing blind border" that the approach taken here should be wholeheartedly commended. This book is essentially a review, but a rather special review.